The role of digital technologies in increasing the competitiveness of branded products - N. V. Kokoreva; E. V. Krasnov; S. A. Silina (Вестник университета)
The article is devoted to the problem of brand promotion management in accordance with the 2030 Agenda for Sustainable Development adopted by UN for years 2016–2030 for all countries of the world. The authors of the article point out that in the new realities implying an intensive use of digital and Internet technologies in communication processes, there is a problem of the carbon footprint increasing due to the use of the Internet and its supporting systems. The necessity and possibility of leveling digital garbage through effective brand communications management are examined. The study is based on the use of general scientific methods. According to the conclusion of the authors, when creating a brand communication system, organizations should competently approach the development of annual promotion programs, taking into account the sustainable development agenda as much as possible. The novelty of the study lies in the development of the structure and content of a brand promotion program whose use will make it possible for a company to form long-lasting relationships with its customers and other stakeholders, which can be based on creating additional value in the process of jointly solving tasks in order to achieve sustainable development goals. In the structure of the brand promotion program proposed, a special place is given to analytics that allow to define achievable goals and identify target groups ready to cooperate in the pursuit of common goals, creating additional value. The findings of the study can be applied by companies interested in brand capital growth through strengthening the brand’s position in the experience of consumers and the public as well as establishing the idea that the brand is sustainable and socially responsible.